Impacts of Climate Change and Remote Sensing Technology in its Mitigation Options through Forest Management - Tamrakar, Rabindra Man (Journal on Geoinformatics, Nepal, 2011)
Greenhouse effect causes global warming and its main consequence is the climate change. Average global temperature is rising significantly over the period. Despite the contribution of total GHG emission by Nepal to the global community is insignificant compared to the developed countries, Nepal has already encountered several adverse effects due to the global climate change, leading to the melting of Himalayan glaciers, reduced agriculture production, loss of biodiversity and ecosystems and changes in social structure and livelihoods. Forest land use change is responsible for CO2 emissions. Forest management therefore can play a significant role in climatic change mitigation. REDD has become the key mechanism in mitigating climate change. The success of REDD mechanism however depends primarily on availability of reliable forestry data including biomass changes and forest carbon estimates. Various Remote Sensing data including optical sensor data have been used for the analysis of forest cover change and estimation of degree of deforestation and degradation. LiDAR however has been widely used in estimating forest biomass for the climate change mitigation.